To be or not to be: an insight into the relationship between standard English and non-standard varieties of English - Hafriza Burhanudeen (Penerbit UKM, 2004)
This paper has two objectives; firstly, to contribute to research on the variation between full and contracted forms of inflected copula/auxiliary be in conversations among native speakers of English and secondly to test whether generalities and inferences made in the late 1960s to 1980s by Labov, the ‘father’ of secular linguistics in this area, and then Rickford and Wolfram can still hold its own in relation to some data collected by the writers in the 1990s. Work in this area of sociolinguistics was initiated by Labov (1969), who analyzed copula/auxiliary contraction and deletion in Vernacular Black English (VBE). Labov found that is and are deletion are possible in VBE only in environments where contraction is possible in SE. He also showed that contraction and deletion in white speech (that is, SE) favor the same grammatical categories in the following complement.Following Labov’s work, a number of other studies have compared deletion and contraction in VBE with white non-standard (WNS) contraction (Labov et al. 1968; Wolfram 1969; Fasold 1972; Wolfram 1974; Rickford 1988. Few studies to date have specifically compared VBE with SE, hence the use of classic references in this paper. An exception is the paper by Fasold and Nakano presented in 1989. The copula/auxiliary is an important feature in such a comparison because of its use as evidence in the divergence hypothesis, which asserts that VBE is a decreolized creole currently developing separately from white SE (Rickford 1988:2). The findings for this paper include the suggestion that the phonetic environments examined appeared to have little or no effect on copula/auxiliary contraction, and the same was true of following constituent environments. Preceding constituent environments, by contrast, clearly had an influence on copula/auxiliary contraction. The findings indicate that the inferences made by pioneers in the field can still claim their own in relation to research done in the 1990s.